von Willebrand factor deficiency leads to impaired blood flow recovery after ischaemia in mice - de Vries, Margreet R.; Peters, Erna A. B.; Quax, Paul H. A.; Nossent, A. Yaël (Thrombosis and Haemostasis, 2017)
Neovascularisation, i. e. arteriogenesis and angiogenesis, is an inflammatory process. Therefore attraction and extravasation of leukocytes is essential for effective blood flow recovery after ischaemia. Previous studies have shown that von Willebrand factor (VWF) is a negative regulator of angiogenesis. However, it has also been shown that VWF facilitates leukocyte attraction and extravasation. We aimed to investigate the role of VWF in arteriogenesis and angiogenesis during post-ischaemic neovascularisation. Wild-type (WT) and VWF deficient (VWF-/-) C57BL/6 mice were subjected to hindlimb ischaemia via double ligation of the left femoral artery, and blood flow recovery was followed over time, using Laser Doppler Perfusion Imaging. Blood flow recovery was impaired in VWF-/- mice. After 10 days, VWF-/- mice showed a 43 ± 5% recovery versus 68 ± 5% in WT. Immunohistochemistry revealed that both arteriogenesis in the adductor muscles and angiogenesis in the gastrocnemius muscles were reduced in VWF-/- mice. Furthermore, leukocyte infiltration in the affected adductor muscles was reduced in VWF-/- mice. Residual paw perfusion directly after artery ligation was also reduced in VWF-/- mice, indicating a decrease in pre-existing collateral arteriole density. When we quantified collateral arterioles, we observed a 31% decrease in the average number of collateral arterioles in the pia mater compared to WT mice (57 ± 3 in WT vs 40 ± 4 pial collaterals in VWF-/-). We conclude that VWF facilitates blood flow recovery in mice. VWF deficiency hampers both arteriogenesis and angiogenesis in a hindlimb ischaemia model. This is associated with impaired leukocytes recruitment and decreased pre-existing collateral density in the absence of VWF.
Keywords: von Willebrand factor; arteriogenesis; angiogenesis; ischaemia; neo-vascularisation